An Electromagnetic Circuit Design to Improve a Multi-Stage Coil-Gun’s Energy Conversion Efficiency - Seonmyeong Kim; Jinho Kim (Applied Sciences, 2022)
We present in this paper a method of improving a coil gun circuit’s energy efficiency and acceleration performance. Particularly, the improvement was performed by designing a solenoid coil and capacitance for projectile velocity enhancement in a multi-stage coil gun, based on simulations and experiments. A projectile decelerates in coil guns when passing through the solenoid coil’s center by being subjugated to a force opposing the launch direction. Thus, we achieved the efficient distribution of the electromagnetic power delivered from the circuit to the projectile by adjusting the capacitance according to the solenoid coil’s shape. This produced a current shape suitable for projectile acceleration, consequently enhancing its performance. Designing the coil using 1.3 mm diameter copper wires, among the coils using copper wires of various diameters, to increase the number of turns and reduce the capacitance improved the energy efficiency while enhancing the acceleration performance. Finally, each stage’s measured and simulated velocities in the coil gun were analyzed and compared. Accordingly, we arrived at an efficient design method for multi-stage coil gun systems.